2013
DOI: 10.1159/000338049
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Tramadol with Minocycline Exerted Synergistic Effects on a Rat Model of Nerve Injury-Induced Neuropathic Pain

Abstract: Neuropathic pain is a refractory clinical problem. Certain drugs, such as tramadol, proved useful for the treatment of neuropathic pain by inhibiting the activity of nociceptive neurons. Moreover, studies indicated that suppression or modulation of glial activation could prevent or reverse neuropathic pain, for example with the microglia inhibitor minocycline. However, few present clinical therapeutics focused on both neuronal and glial participation when treating neuropathic pain. Therefore, the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…It has been observed in our previous report that coadministration of tramadol and minocycline indicated synergistic effects on peripheral nerve injury-induced neuropathic pain [13]. Consequently, the present study suggests that suppressing peripheral nerve injury-induced aberrant activation of the spinal dorsal horn IL-1β-related pathway contributes to the underlying mechanism of the synergistic effects of tramadol and minocycline coadministration on peripheral nerve injury-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It has been observed in our previous report that coadministration of tramadol and minocycline indicated synergistic effects on peripheral nerve injury-induced neuropathic pain [13]. Consequently, the present study suggests that suppressing peripheral nerve injury-induced aberrant activation of the spinal dorsal horn IL-1β-related pathway contributes to the underlying mechanism of the synergistic effects of tramadol and minocycline coadministration on peripheral nerve injury-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 71%
“…Normal saline (0.9%) was used as the negative control. The dose for intrathecal administration (tramadol 10 μg/rat, minocycline 30 μg/rat or combination tramadol 3.9 μg/rat + minocycline 27.3 μg/rat) was based on our previous study [13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent study by Mei et al (2013b) indicated that under conditions of neuropathic pain, spinal IL-1beta is diminished by minocycline administration, a finding that supports our idea that IL-1beta may be one of the key factors in neuropathic pain. Interestingly, a combination of tramadol and minocycline exerted synergistic effects in a rat model of neuropathic pain (Mei et al, 2013a). Similarly, the administration of the p38 inhibitor SB203580 also markedly alleviated mechanical allodynia by reducing injury-induced increases in the expression of IL-1beta (Mei et al, 2013b).…”
Section: Discussionmentioning
confidence: 97%
“…Tra has been combined with other drugs, e.g., dexmedetomidine [Farghaly et al, ], propentofylline [Zhang et al, ], minocycline [Mei et al, ], doxepin [Uyar et al, ], dexmedetomidine [Guneli et al, ] to generate synergistic interactions. Tra and venlafaxine in combination are additive in producing antihyperalgesic and anti‐allodynic effects [Uyar et al, ; Wrzosek et al, ].…”
Section: Discussionmentioning
confidence: 99%